Wideband and Multiband Antenna Design and Fabrication for Modern Wireless Communications Systems - Adit Kurniawan; Salik Mukhlishin (LPPM ITB, 2013)
One of the major challenges due to spectrum scarcity in modern wireless communication is on antenna design that can serve a non-contagious frequency spectrum. In this paper, wideband and multiband design approaches are proposed to produce antennas that can serve various wireless technologies using different frequencies from 2.3 to 6.0 GHz, covering WiFi frequencies at 2.4-2.48 GHz, 5,15-5,35 GHz and 5,725-5,825 GHz, as well as WiMax frequencies at 2.3-2.4 GHz, 2.495-2.695 GHz, 3.3-3.8 GHz, and 5.25-5.85 GHz. The wideband and multiband antenna were implemented on an 0.8 mm thick of FR4 epoxy dielectric substrate with permittivity Îµr=